The readiness of PJOK Teachers in the virtual learning in Covid-19 era in the Public Junior High Schools of Pegandon, Kendal in the academic year of 2020 - Risma Ayu Tryana; Sunardi Sunardi; Abdul Aziz Purnomo Shidiq (PJKR FKOR UNS, 2020)
This study aims to discover the readiness of PJOK or sport teachers in the virtual learning in the era of covid-19 in public junior high schools of Pegandon, Kendal. This study uses qualitative method with descriptive approach. This approach is chosen by the writer because it describes the situation of particular events based on the facts that appear as it should be. The subjects of this study are 8 PJOK teachers in the public junior high school of Pegandon. This study uses two types of data, namely primary data and secondary data. The data collecting techniques used in this study are observation, questionnaire, and documentation techniques. The data obtained from the result of questionnaire is analyzed and examined its data validity using SPSS 22 program. The result of this study can be concluded that the level of teachers’ readiness in the virtual learning in covid-19 era in the public junior high school of Pegandon can be considered as ready in delivering the learning material virtually. It has average percentage of 75%. For teachers who are considered as not ready in delivering the learning material virtually have the percentage of 25% because there are only 2 teachers who are considered as not ready to deliver the learning material virtually. It is caused by the condition of the schools that are isolated, lack of signal, and other causes It can be concluded that the result of of this study is used as knowledge and application for PJOK teachers in the public junior high school in Pegandon regarding on how to provide the PJOK teaching material or learning material which still run properly and correctly in this era of covid-19 even it cannot be conducted in face-to-face method and must be conducted online. The readiness of PJOK teachers is important for the learning development of students in the application of virtual PJOK learning.